Modern Scientific Research on the Development of Proactiveness of Preschool Children - Agiliar Tukler, Victoria (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
This article introduces the results of analysis of modern scientific research in preschool education, which represents the problem of development of basic qualities of the identity. The research displays that the results of the study on the problem of development of basic qualities of preschool-age children influence the improvement of the content of program provision in the educational process in preschool educational institutions in Ukraine and are meant to be a reference point in choosing the strategy of its reorganization